Aquaporins: A new target for traditional Chinese medicine in the treatment of digestive system diseases - Yuchan Huang; Yuchan Huang; Yuchan Huang; Shidu Yan; Shidu Yan; Shidu Yan; Zixia Su; Zixia Su; Zixia Su; Lei Xia; Lei Xia; Lei Xia; et al. (Frontiers Media S.A., 2022)
Aquaporins (AQPs) are a family of transmembrane proteins expressed in various organ systems. Many studies have shown that the abnormal expression of AQPs is associated with gastrointestinal, skin, liver, kidneys, edema, cancer, and other diseases. The majority of AQPs are expressed in the digestive system and have important implications for the physiopathology of the gastrointestinal tract as well as other tissues and organs. AQP regulators can prevent and treat most gastrointestinal-related diseases, such as colorectal cancer, gastric ulcer, and gastric cancer. Although recent studies have proposed clinically relevant AQP-targeted therapies, such as the development of AQP inhibitors, clinical trials are still lacking and there are many difficulties. Traditional Chinese medicine (TCM) has been used in China for thousands of years to prevent, treat and diagnose diseases, and is under the guidance of Chinese medicine (CM) theory. Herein, we review the latest research on the regulation of AQPs by TCMs and their active components, including Rhei Radix et Rhizoma, Atractylodis macrocephalae Rhizoma, Salviae miltiorrhizae Radix et Rhizoma, Poria, Astragali radix, and another 26 TCMs, as well as active components, which include the active components include anthraquinones, saponins, polysaccharides, and flavonoid glycosides. Through our review and discussion of numerous studies, we attempt to explore the regulatory effects of TCMs and their active components on AQP expression in the corresponding parts of the body in terms of the Triple Energizer concept in Chinese medicine defined as "upper energizer, middle energizer, and lower energizer,"so as to offer unique opportunities for the development of AQP-related therapeutic drugs for digestive system diseases.